The Contemplative Practitioner - JOHN P. MILLER (University of Toronto Press, 2013)
You have in your hands an introduction to a set of practices and a way of being that many of us are seeking as our lives become more fragmented, our attention drawn to one screen or decision after another, and our very earth threatened by ever-new challenges. Not only is this an introduction to contemplative methods for bringing a centred, clear insight and a kind heart to each moment but also, and most unusual, it shows us how to bring contemplative awareness into our work in the world, from education to a range of other professions. Contemplative practices come from traditions all over the world. Examples include various forms of meditation, time in nature, writing, contemplative arts, and contemplative movement, including yoga. They cultivate a critical, irst-person focus, sometimes with direct experience as the object, at other times concentrating on complex ideas or situations. Contemplative methods incorporated into daily life connect us to what we ind most meaningful as they help us quiet our minds in the midst of action and distraction. Recent research has shown that contemplative practices can reduce stress and enhance creativity as well as develop capacities for deep concentration, greater empathy, communication, and improved focus and attention. In recent years at the Center for Contemplative Mind in Society, we have seen these practices result in changes in how people make their living as well as how they live. Engineers at Google, trained in mindfulness, listen more fully to each other and discover more creative uses of their technology.